HOLISTIC APPROACH IN ELT: LIFE EDUCATION THROUGH ENGLISH LANGUAGE LEARNING - Ginanjar Arif Wijaya (UAD TEFL International Conference)
As the integral part of education, English language teaching has taken too little part of it and brought it to the level where English learning seems to talk only about English. In another extent, English for specific purpose declares its specialty to satisfy the demand of workforce. Researches in ELT are also commonly propelled by the urges to counter the work challenges and to answer the questions of how English can effectively be acquired. Reductionism roots as the problem. This tendency is then strengthened by the education system that leaves the teachers with not many options, systematically forcing the language learners to merely surpass the minimum standard score of English language subject. Within ecological and humanity crises, ELT needs to contribute more than just enabling the learners to communicate well or preparing them for works. ELT needs to take broader scope in order to induce life enlightenment, educate life skills, nurture humanity, and maintain the planet. Such enormous scope cannot be maintained by the current reductionistic approach. Therefore, holistic approach in ELT that integrates it with the whole network of life appears as the solution for this problem.